Associations of dietary choline intake and kidney function with hyperuricemia in Chinese children and adolescents: a cross-sectional studyResearch in context - Chengping Li; Jing Li; Zhiquan Diao; Lianhong Chen; Siwen Yu; Lianlong Yu; Qianrang Zhu; Xiaomei Dong; Yiya Liu; Tao Liu; Dan Liu (EClinicalMedicine)
Summary: Background: Limited studies have suggested an effect of dietary choline intake on uric acid levels. We aim to investigate the associations between choline intake and hyperuricemia (HUA), as well as the mediating role of kidney function in this relationship, among the Chinese population aged 6–17 years. Methods: Participants were divided into quartiles according to residual energy-adjusted dietary choline intake in our cross-sectional study. Dietary choline intake was assessed using the 24-h dietary recalls method over three consecutive days, including two weekdays and one weekend day. The primary outcome was the HUA prevalence. Based on recommendation in Clinical Paediatric Nephrology (3rd ed), HUA is defined based on fasting serum uric acid levels, with cutoffs varying by age and sex. The associations between choline intake and HUA were analysed using weighted logistic regression models, restricted cubic spline models, and linear regression models. The mediated proportions of estimated glomerular filtration rate (eGFR) in the associations were estimated with mediation effect models. The data for this study were collected from the China National Nutrition and Health Surveillance of Children and Lactating Mothers (2016–2017) conducted between October 2016 and December 2018. Eligible participants were identified through a database search conducted from October to December 2023. Findings: Among the 10749 participants, 3398 (31.6%) individuals were found to have HUA. A negative dose-dependent relationship was found between dietary choline intake and HUA. Compared to participants in the lowest intake quartile of total choline, phosphatidylcholine, and betaine, those in the 4th quartile had lower odds of HUA, with odds ratio (OR) of 0.75 (95% confidence interval [95% CI], 0.63–0.90), 0.75 (95% CI, 0.64–0.89), and 0.75 (95% CI, 0.59–0.94), respectively. The eGFR mediated 10.60%–14.58% of the associations. Participants in the 4th quartile of lipid-soluble dietary choline exhibited 24.00% reduced odds of HUA compared to those in the lowest intake quartile, with an OR of 0.76 (95% CI, 0.64–0.90). Interpretation: Moderate to high intake of dietary choline (181.20–357.92 mg/d), particularly phosphatidylcholine (120.22–207.58 mg/d), and betaine (189.24–282.37 mg/d), may reduce the odds of HUA by improving glomerular filtration function. Further interventional studies are needed to establish causal relationships. Funding: This work was supported by the National Natural Science Foundation of China (82003443, 42375180), the Natural Science Foundation of Guangdong Province of China (2024A1515012088), and the Construction of High-level University of Guangdong (G624330422).